Financial Analysis of Surimi Processing by Modern and Semi-Modern Scale - Nazori Djazuli; Mita Wahyuni; Daniel Monintja; Ari Purbayanto (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2009)
Development of surimi processing in the industry regions which have huge potential of rawmaterial, can be done through aiming at the business feasibility existed either by modern surimi processingbusiness as weel as semi modern. In general, theaim of this research is to analyze the feasibility business ofsurimi processing either by modern surimi processing business or semi modern. Sampling of surimiprocessing business for modern surimi processing was located in Pekalongan, Central Java Province andsemi modern surimi processing was located in Pulau Moro, Riau Island Province. Data collection was doneby questionnaire and interview to stakeholders of surimi processing industry. Method of analysis wascarried out by using criteria of financial feasibility i.e. Payback Period (PB), Net Present Value (NPV),Internal Rate of Return (IRR), Profitable Index (PI), Net B/C, and Break Event Point (BEP). Result ofresearch showed that surimi processing business either by modern surimi processing business or semimodern is feasible shown from (1) Value of NPV for PT. A is Rp.22,647,400,670 and PT.B isRp.29,866,797,485 for 10 years, (2) Value of IRR at surimi business in PT.A is 49.28% and PT.B is56.11%, (3) PT. A needs 2 years 1 month and 6 days to return the investment that has been invested insurimi processing, meanwhile PT.B needs 1 year 10 months and 6 days, (4) Value of profitability indexPT.A is 2.43 and PT.B is 2.78, and (5) figure of Net B/C Ratio PT.A is 1.89, and PT.B has figure of NetB/C Ratio 1.58.Keywords : financial feasibility, surimi product